Counseling on The Benefits of Eating Vegetables for The Health of The Body - Rigyalfa Da Wafi; Asep Bayu Dani Nandiyanto (Indonesian Journal of Educational Research and Technology, 2023)
This study was conducted to socialize about the benefits, types, and content of vitamins contained in vegetables that are commonly consumed by youth organizations/Karang Taruna members. Learning is done using PowerPoint media and its exposure is assisted by Zoom Meeting media and Whatsapp groups. And in this study, we spread 20 questions of pretest questionnaires before socialization and 20 post-test questions after socialization. The target of this study is a member of the organization Bulog Complex, Bekasi, Indonesia which consists of as many as 20 people. The results of the study conducted by the authors showed that members of the organization are interested in gaining deeper knowledge about vegetables, and want to be more routine to eat vegetables after getting socialization. This study concludes that most members of the Youth organization are interested in knowing more about vegetables and their benefits.